2012
DOI: 10.5812/ijhrba.5336
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Dependency

Abstract: The prevalence of Methamphetamine use and related disorders increased. There are currently no pharmacological treatments for symptoms of Methamphetamine related disorders, because our knowledge about the cellular and molecular mechanisms of Methamphetamine induce psychosis and dependency is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Participants were regular MA users with multiple problems such as divorce, unemployment and poly use of other illicit drugs. This is consistent with some studies which indicate that drug-using women in methadone treatment frequently report divorce, low socio-economic status and unemployment (4,5,22,23). Consistent with other studies (22,23), most participants had initiated drug use with alcohol, opium and cannabis before transitioning to heroin and MA use.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Participants were regular MA users with multiple problems such as divorce, unemployment and poly use of other illicit drugs. This is consistent with some studies which indicate that drug-using women in methadone treatment frequently report divorce, low socio-economic status and unemployment (4,5,22,23). Consistent with other studies (22,23), most participants had initiated drug use with alcohol, opium and cannabis before transitioning to heroin and MA use.…”
Section: Discussionsupporting
confidence: 79%
“…A study of 150 male and female methadone patients in Tehran indicated that 15%, 24%, and 12% of the respondents were MA users while in treatment in months one, three, and six respectively (3). A study at a methadone clinic in Zahedan indicated that MA use increased among patients from six percent in 2009 to approximately 20% in 2011 (4). A study of 190 opioiddependent women at a methadone clinic in Mazandaran indicated that 25% of the participants were regular MA users (5).…”
Section: Introductionmentioning
confidence: 99%
“…A study at a methadone clinic, found that methamphetamine use increased among treatment seekers from six percent in 2009 to approximately 20% in 2011 (Lashkaripour and Torbati, 2012). A study of 378 treatment seekers at a therapeutic community center found that 6.6% had positive methamphetamine urine specimens in treatment (Sadir et al, 2013).…”
Section: Methamphetamine Use In Opiate Use Treatmentmentioning
confidence: 97%
“…Their misconceptions were likely to originate from lack of knowledge or poor ATS education. Poor knowledge of the side effects of ATS can be a strong motivation to self-treatment with ATS use or its common use in the community (11)(12)(13)(14)(15)(16). Therefore, the provision of educational programs is suggested for this group.…”
Section: Discussionmentioning
confidence: 99%